3D-printed β-TCP bone tissue engineering scaffolds: Effects of chemistry on in vivo biological properties in a rabbit tibia model. Issue 14 (27th July 2018) - Nandi, Samit Kumar; Fielding, Gary; Banerjee, Dishary; Bandyopadhyay, Amit; Bose, Susmita
Abstract: Abstract : In this study, the effects of 3D-printed SiO2 and ZnO-doped tricalcium phosphate (TCP) scaffolds with interconnected pores were evaluated on the in vivo bone formation and healing properties of a rabbit tibial defect model. Pure and doped TCP scaffolds were fabricated by a ceramic powder-based 3D printing technique and implanted into critical sized rabbit tibial defects for up to 4 months. In vivo bone regeneration was evaluated using chronological radiological examination, histological evaluations, SEM micrographs, and fluorochrome labeling studies. Radiograph results showed that Si/Zn-doped samples had slower degradation kinetics than the pure TCP samples. 3D printing of TCP scaffolds improved bone formation. The addition of dopants in the TCP scaffolds improved osteogenic capabilities when compared to the pure scaffolds. In summary, our findings indicate that the addition of dopants to the TCP scaffolds enhanced bone formation and in turn leading to accelerated healing.